Pengaruh Relaksasi Progresif Terhadap Tekanan Darah Lansia Hipertensi Yang Mendapat Senam Lansia Di Wilayah Kerja Puskesmas Purwosari - Wulandari, Esti; , Arina Maliya, S.Kep., Ns.,M.Si., Med (2017)
Hypertension is an abnormal increase in blood pressure in the arteries continuously for more than one period. Hypertensive disease ranks first in the group of elderly non-communicable diseases compared to other diseases. There are two ways of treatment of hypertension that is by pharmacological and non pharmacological. Pharmacological treatment can cause side effects that are not good for the body, while the non-pharmacological does not have side effects on the body. Non-pharmacological treatment may include gymnastics and progressive relaxation. This study aimed to determine the effect of progressive relaxation and exercise on blood pressure of elderly hypertensive elderly in Puskesmas Purwosari. This type of research is quantitative withdesign quasyexperiment with the design of the study one group pretest-posttest control design. The study was conducted in April 2017 for 3 weeks in Puskesmas Purwosari. The samples used by 30 respondents consisting of 15 experimental group and the control group 15 in accordance with the criteria and purposivesampling.Collecting data using mercury blood pressure meter by measuring blood pressure and analysis of data by WilcoxonSigned Rank Test. Based on the research results indicate that there is a progressive relaxation effect on the blood pressure of hypertensive elderly in Puskesmas Purwosari ie systolic pre test experimental group averaged 158,67mmHg then post test experimental group the average 150,33mmHg. As for the pre test diastole experimental group the average of 100,67mmHg, then to post test experimental group diastole the average of 94,00mmHg with significant values (p-value) 0,000 systole-diastole, while the significant value (p-value) 0,002 resulting in decreased blood pressure in the experimental group. Keywords: elderly, blood pressure, exercise elderly, progressive relaxation.